The impact of exurbanism on infrastructural facilities in Bangsar, Kuala Lumpur - Hiong, Lai Yee; Syed Salim, Azizah Salim (Universiti Putra Malaysia, 2012)
Exurbanism is influenced by the way a city is being planned. Besides, exurban form is also interrelated to the environment, functionality, and economic development, social and cultural structure of a city. This study will discuss the extent of exurb development in Bangsar, Kuala Lumpur. Theory-guided content analysis is applied where the initial presupposition in the analysis was that the subject matter of the study depicted the studied phenomenon. The purpose of the study was to investigate the exurbanism in Bangsar and seeks the relationship between exurbanism and permeability of infrastructural facilities. Hence, suitable planning of infrastructural facilities in terms of accessible roads to improve permeability in exurb Bangsar can be identified. The study produces a clear description of the phenomenon, and arrange in an organize form without losing the information contained therein. The study leads on how future Bangsar should look in the globalization age. Bangsar can be made more liveable with a better exurb living quality by fostering the cultural values and community lifestyles that creates the sense of place in the future.